The effect of partnership and information and communication technology (ICT) capability on competitive advantage through entrepreneurial marketing: a study on culinary sector SMEs in Batam City - Husna, Asmaul; Alfatiha, Raja Ainaya; Chan, Arianis; Muftiadi, Anang (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study analyzes the influence of partnership and Information and Communication Technology (ICT) capability on competitive advantage through entrepreneurial marketing. The research employs a quantitative approach with descriptive analysis, involving data collected through questionnaires, interviews, and observations from 56 culinary sector SMEs in Batam City. The data analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that partnership and ICT capability positively and significantly affect entrepreneurial marketing, enhancing coordination and technology usage among SMEs. However, these variables do not significantly impact competitive advantage directly. On the other hand, entrepreneurial marketing demonstrates a positive and significant influence on competitive advantage, highlighting the importance of strong customer relationships and high-value product creation. Additionally, ICT capability significantly influences competitive advantage through entrepreneurial marketing, emphasizing the role of technology in enhancing business flexibility and marketing capabilities.